Jamieson, N. (2023). Darkest Before Dawn: Australian Veterans’ Accounts of Moral Injury - Bakhurst, Melissa G; Carey, Lindsay B (Health and Social Care Chaplaincy, 2025)
Jamieson, N. (2023). Darkest Before Dawn: Australian Veterans’ Accounts of Moral Injury. Canberra: Amazon Books Australia, 141 pp. (pbk). ISBN: 9781962464482.